Properties of magnesium doped nanocrystalline hydroxyapatite synthesize by mechanochemical method - S., Adzila; S., Ramesh; I., Sopyan (Asian Research Publishing Network (ARPN), 2016)
The sintering behaviour of Magnesium-doped nanocrystalline hydroxyapatite (MgHA) synthesized by mechanochemical method was investigated over the temperature range of 1000 oC to 1300 oC. The properties were investigated in terms of phase stability, bulk density and Vickers hardness. In the present research, a dry mechanochemical synthesis was successfully employed to synthesis a nanocrystalline MgHA powder without any secondary phases. Lower sintering temperature at 1000 oC produced β-TCP phase in MgHA in all concentrations. Hence, doping Mg2+ into HA has induced the formation of brushite and α-TCP where these phases were averagely increased with Mg2+ concentration. Increasing Mg2+ concentrations have led to the decreased of HA phase and increased the secondary phases.Mg2+ did not significantly improved the density of HA as the density decreased with Mg2+ doping at 1200 oC – 1250 oC. However, Mg2+ increased the hardness of HA when sintered from 1000 oC to 1300 oC. The maximum hardness was obtained by 3% MgHA sintered at 1250 oC with 5.47 GPa.